The More the Merrier? Detecting Impacts of Bank Regulation After the Global Financial Crisis - Christian Kalhoefer; Guenter Lang (Credit and Capital Markets – Kredit und Kapital, 2019)
Governments worldwide reacted swiftly to the global financial crisis by tougher regulations. This paper investigates the impacts of the regulatory environment on operating costs using panel data of 2,200 German banks over the timeframe from 1999 to 2014. We estimate cost functions with and without proxies for regulation and analyze the results with respect to period, bank size, and group affiliation. Our results show that regulatory costs were peaking in 2001, 2008, and lately since 2012. Most interesting, however, is the asymmetry of regulation: Whereas the cost effects were symmetric for all banks until 2003, the last ten years were different. Larger institutions and savings banks could neutralize the impacts of increasing regulation on operating costs. In contrast, smaller banks, especially if they are cooperative banks, were facing significant cost increases. We therefore expect unintended structural shifts like a reduction in the diversity of banks, which are negative for competition, service quality, and for the stability of the financial system. – – Weltweit wurde als Folge der globalen Finanzkrise die Regulierung des Finanzsektors verschärft. Dieser Beitrag geht der Frage nach, welche Konsequenzen diese Regulierungsmaßnahmen für die operativen Kosten im Bankengeschäft haben. Auf der Basis von Paneldaten von 2,200 in Deutschland aktiven Banken über den Zeitraum von 1999 bis 2014 schätzen wir Kostenfunktionen mit und ohne Proxies für Regulierung und werten die Ergebnisse nach Beobachtungsjahr, Bankengröße, und Gruppenzugehörigkeit aus. Unsere Ergebnisse zeigen Kostenspitzen in den Jahren 2001, 2008, und zuletzt seit 2012. Am interessantesten sind jedoch die asymmetrischen Effekte der Bankenregulierung: Während unsere Modelle bis einschließlich 2003 nahezu gleichmäßige Kostenbelastungen anzeigen, änderte sich dies deutlich mit dem Jahr 2004. Im Gegensatz zu großen Institute und Sparkassen, die die Regulierungskosten nahezu neutralisieren konnten, sahen sich kleine Institute und Genossenschaftsbanken mit deutlichen Kostensteigerungen konfrontiert. Als Folge dieser asymmetrischen Kostenwirkungen staatlicher Bankenregulierung erwarten wir unbeabsichtigte Strukturveränderungen wie z.B. Konzentrationsprozesse, die sich negativ auf Wettbewerb, Dienstleistungsqualität, und letztendlich auch negativ auf die Stabilität des gesamten Finanzsystems auswirken werden.
Keywords: G21; G38; 330; Banks; Regulation; Operating Costs; Germany; Cost Function; Global Financial Crisis